Effectiveness and Cognitive Changes With Ultrabrief Right Unilateral and Other Forms of Electroconvulsive Therapy in the Treatment of Mania. Issue 1 (March 2019) - Wong, Vincent Khung Hoon; Tor, Phern Chern; Martin, Donel M.; Mok, Yee Ming; Loo, Colleen
Abstract : Objective: Electroconvulsive therapy (ECT) is an effective treatment in mania. However, there is little evidence regarding the use of ultrabrief right unilateral (RUL-UB) ECT in treatment of acute manic episodes. The aim of this study was to report on the effectiveness and cognitive profile of ECT in bipolar mania, including a sample who received RUL-UB ECT. Methods: This naturalistic study retrospectively collected data in 33 patients who received ECT with concurrent antipsychotics for mania between October 1, 2014, and July 30, 2016. Electroconvulsive therapy was given using RUL-UB, brief-pulse right unilateral, or brief-pulse bitemporal approaches, dosed according to the patient's seizure threshold. The Brief Psychiatric Rating Scale (BPRS), Young Mania Rating Scale (YMRS) score, and the Montreal Cognitive Assessment (MoCA) were administered to patients before and after the ECT course. Results: For the whole sample, there was a significant improvement in BPRS (total score and manic subscale), YMRS, and MoCA total scores across the ECT treatment course. The overall BPRS response rate was 84%, and mean scores decreased from 42.1 (SD, 12.0) to 26.0 (SD, 4.0). The 13 patients who received RUL-UB ECT also showed significant improvement in BPRS, YMRS, and MoCA scores over the treatment course. Conclusions: Electroconvulsive therapy in general and also specifically RUL-UB ECT were effective in treating mania and also led to global cognitive improvement. Abstract : Supplemental digital content is available in the text.